Art photography: Ideation and influences of Islamic geometric patterns / Azmil Aswad Che Mat, Aidah Alias and Farihan Zahari - Che Mat, Azmil Aswad; Alias, Aidah; Zahari, Farihan (2017)
Photography is a very broad communication style used in our society and it is a way of communicating as in visual style of expression to touch others in various ways. This is a process of creation, activity and art creating something for others to value and appreciate the captured image of photography. The Shari‘ah of Islam has not permitted creating pictures of living things or even taking pictures of them. The objectives of this research is to explore the ideation of Islamic geometric patterns and to be experimenting with the geometric Islamic patterns style into art photography. This study also examines the possibilities of creating art photographic influences with the geometric Islamic patterns. Experimental approach in terms of using adobe Photoshop was used to conduct the study. The photography images produce for this research is only scope on modern architecture. It is to understand the Islamic geometric pattern and implement its characteristic into photography to create symmetry patterns in art photography. The result gathered from this research contributes towards of enhancement and creating new art photography with modern architecture and Islamic art approach, creating pattern variation and innovation.